Pemanfaatan local content suatu perguruan tinggi: suatu analisis terhadap repository Perpustakaan Universitas Islam Negeri Sumatera Utara Medan. - Sri Melani (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
This article entitled Utilization of Local Content Activity of a Higher Education: An Analysis Toward the Repository of the Islamic University Library of North Sumatra State. The purpose of this article is to determine the effect of the utilization (local content) on the lectures at the library of the State Islamic University of North Sumatra. The method used in this study is qualitative with the type of case study research Data collection techniques that is by observation observation. The results of the research have concluded that, the utilization of local content collection is very influential in lecturing activities of students who are doing college tasks. The effect of the utilization of local content collection, among others, is as reference material; secondary information sources, thesis writing guide, reference materials and inspiration in doing lecture work.Keywords: Local Content, College, Medan